Evaluación de la calidad y propiedades fisicoquímicas y microbiológicas de las quebradas Lupunilla y Masana – Distrito de Belén – Iquitos – 2024 - Coral Guerra, Miguel Ángel (2024)
In the district of Belén, Iquitos, the Lupunilla and Masana streams are important sources of water, however, they present significant levels of contamination due to anthropogenic activities. The research, carried out in 2023, evaluated the physicochemical and microbiological properties of the water in both streams to compare them with the environmental quality standards (ECA) of Peru. The physicochemical properties of the waters analyzed revealed the following: The pH varies between 6.22 and 7.04; the electrical conductivity is between 65.8 and 97.2 μS/cm; Total dissolved solids reach values of up to 48.8 mg/L. A total hardness of up to 542.5 mg/L was found in the growing season. Regarding alkalinity, it varies between 0.6 and 1.25 mg/L of CaCO3, while chlorides have values between 4.87 and 10.64 mg/L. Turbidity and color also showed significant variations, with a maximum of 687.5 nephelometric units (NTU) and 458.33 platinum-cobalt color units (UVC). In microbiological terms, total coliform bacteria counts range between 110 and 940 NMP/100 mL, while fecal or thermotolerant coliforms range between 4 and 460 NMP/100 mL. These levels are within the values mentioned in the ECA, which reflects the need for disinfection treatments to guarantee the drinkability of the water. Seasonal differences in water quality are related to variations in precipitation, which increase turbidity and dissolved solids concentration during the growing season. These results provide crucial evidence for the management of local water resources and suggest the implementation of more rigorous sanitation plans.